Mills-Symon Oral History Part 3 - Symon, Keith; Mills, Fred (My University, 2009)
Part 3 of an oral history with Fred Mills, ex director of the Physical Sciences Laboratory , and Keith Symon, ex director of the Synchrotron Radiation Center. Conducted by Esther Olson.
Keywords: Synchrotron, Mills, Symon